2017
DOI: 10.18632/oncotarget.18004
|View full text |Cite
|
Sign up to set email alerts
|

Remarkably similar CTLA-4 binding properties of therapeutic ipilimumab and tremelimumab antibodies

Abstract: Monoclonal antibody based immune checkpoint blockade therapies have achieved clinical successes in management of malignant tumors. As the first monoclonal antibody targeting immune checkpoint molecules entered into clinics, the molecular basis of ipilimumab-based anti-CTLA-4 blockade has not yet been fully understood. In the present study, we report the complex structure of ipilimumab and CTLA-4. The complex structure showed similar contributions from VH and VL of ipilimumab in binding to CTLA-4 front β-sheet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 35 publications
3
66
0
1
Order By: Relevance
“…It is also somewhat surprising that all these PD-L1 blocking antibodies bind PD-L1 on the flat front beta-sheet as generally targeting a relatively flat protein surface is very challenging. When compared with other immune checkpoint blocking antibodies, we have found that CTLA-4 blocking antibodies such as ipilimumab (PDB:5TRU) and tremelimumab (PDB:5GGV) similarly target the front surface of IgV domain of CTLA-4, while PD-1 blocking antibodies such as pembrolizumab (PDB:5GGS) and nivolumab (PDB:5GGR) mainly bind PD-1 on the connecting loops of the front beta-sheet [ 18 , 22 24 ]. It is unclear if the differences in the epitopes of these receptors are due to the differences in antibody screening processes or due to differences in the geometry and electrostatic properties of the IgV domains of these receptors.…”
Section: Resultsmentioning
confidence: 99%
“…It is also somewhat surprising that all these PD-L1 blocking antibodies bind PD-L1 on the flat front beta-sheet as generally targeting a relatively flat protein surface is very challenging. When compared with other immune checkpoint blocking antibodies, we have found that CTLA-4 blocking antibodies such as ipilimumab (PDB:5TRU) and tremelimumab (PDB:5GGV) similarly target the front surface of IgV domain of CTLA-4, while PD-1 blocking antibodies such as pembrolizumab (PDB:5GGS) and nivolumab (PDB:5GGR) mainly bind PD-1 on the connecting loops of the front beta-sheet [ 18 , 22 24 ]. It is unclear if the differences in the epitopes of these receptors are due to the differences in antibody screening processes or due to differences in the geometry and electrostatic properties of the IgV domains of these receptors.…”
Section: Resultsmentioning
confidence: 99%
“…The therapeutic ligands typically bind CTLA4 with higher affinities than natural ligands, which enables their exploitative binding. For example, Ipilimumab (k D ¼ 18.2 nM) and Tremelimumab (k D ¼ 5.89 nM) bind CTLA4 with higher affinity compared to natural ligands (k D,CD86 ¼ 2.6 mM, k D,CD80 ¼ 0.2 mM) (39,40). A mapping between affinities (off rates) to the uptake kinetics of physiological ligands in our model should be made with caution because of the factors that cannot be inferred experimentally and the impact of multivalent avidity affecting ligand binding.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the experience from the melanoma cohort and the CheckMate-data in lung, it does appear that combination therapy can provide a broader, more durable response [ 44 ]. Should the final MYSTIC data not meet the OS end-point, doubt will likely be cast on the efficacy of tremelimumab, an IgG2 antibody with slightly different binding properties to its IgG1 counterpart, ipilimumab, rather than the potential of combination therapy [ 45 ].…”
Section: Immunotherapy In Non-small Cell Lung Cancermentioning
confidence: 99%